Regional variation of Guillain-Barré syndrome - Doets, AY; Verboon, C; Van Den Berg, B; Harbo, T; Cornblath, DR; Willison, HJ; Islam, Z; Attarian, S; Barroso, FA; Bateman, K; Benedetti, L; Van Den Bergh, P; et al. (Oxford Academic, 2018)
Guillain-Barré syndrome is a heterogeneous disorder regarding the clinical presentation, electrophysiological subtype and outcome. Previous single country reports indicate that Guillain-Barré syndrome may differ among regions, but no systematic comparative studies have been conducted. Comparative studies are required to identify factors determining disease susceptibility, variation and prognosis, and to improve diagnostic criteria. The International Guillain-Barré Syndrome Outcome Study is a prospective, observational cohort study including all patients within the diagnostic spectrum, aiming to describe the heterogeneity of Guillain-Barré syndrome worldwide. The current study was based on the first 1000 inclusions with a follow-up of at least 1 year and confirmed the variation in clinical presentation, course and outcome between patients. The full clinical spectrum of Guillain-Barré syndrome was observed in patients from all countries participating in the International Guillain-Barré Syndrome Outcome Study, but the frequency of variants differed between regions. We compared three regions based on geography, income and previous reports of Guillain-Barré syndrome subtypes: 'Europe/Americas', 'Asia' (without Bangladesh), and 'Bangladesh'. We excluded 75 (8%) patients because of alternative diagnoses, protocol violations, or missing data. The predominant clinical variant was sensorimotor in Europe/Americas (n = 387/562, 69%) and Asia (n = 27/63, 43%), and pure motor in Bangladesh (n = 74/107, 69%). Miller Fisher syndrome and Miller Fisher-Guillain-Barré overlap syndrome were more common in Asia (n = 14/63, 22%) than in the other two regions (Europe/Americas: n = 64/562, 11%; Bangladesh: n = 1/107, 1%) (P < 0.001). The predominant electrophysiological subtype was demyelinating in all regions (Europe/Americas: n = 312/573, 55%; Asia: n = 29/65, 45%; Bangladesh: n = 38/94, 40%). The axonal subtype occurred more often in Bangladesh (n = 34/94, 36%) than in Europe/Americas (n = 33/573, 6%) and other Asian countries (n = 4/65, 6%) (P < 0.001). In all regions, patients with the axonal subtype were younger, had fewer sensory deficits, and showed a trend towards poorer recovery compared to patients with the demyelinating subtype. The proportion of patients able to walk unaided after 1 year varied between Asia (n = 31/34, 91%), Europe/Americas (n = 334/404, 83%) and Bangladesh (n = 67/97, 69%) (P = 0.003). A similar variation was seen for mortality, being higher in Bangladesh (n = 19/114, 17%) than in Europe/Americas (n = 23/486, 5%) and Asia (n = 1/45, 2%) (P < 0.001). This study showed that factors related to geography have a major influence on clinical phenotype, disease severity, electrophysiological subtype, and outcome of Guillain-Barré syndrome.